Manajemen Qolbu dalam Perspektif Islam dengan Diary Therapy Pada Siswa di SMP Plus Nurul Hikmah Pamekasan - Iswatun Hasanah (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
This study aims to determine the effect of Qalb management with diary therapy on students at SMP Plus Nurul Hikmah Pamekasan. Using field research with a qualitative descriptive case study approach by trying to understand the Qolbu Management treatment using Diary Therapy. Data collection techniques through in-depth interviews, participatory observation, and documentation studies. The participants were 3 students with different problem conditions and backgrounds. The participants are trained to write down the emotions they feel and keep remembering Allah in their behavior and begin to improve themselves and repent for the sins that have been committed. The results showed that Qolbu management with diary therapy affected the research subject's problems.